PENGARUH MODEL PEMBELAJARAN CASE BASED LEARNING TERHADAP KETERAMPILAN GENERIK SAINS SISWA PADA MATERI MINYAK BUMI - Diyanti, Wafika Rahma; Refelita, Fitri; Kurniawati, Yenni (Journal of Chemistry Education and Integration, 2024)
AbstractScience generic skill is a basic thinking skill needed in learning science. Student science generic skill was on low category, so the appropriate learning model was needed to solve it. This research aimed at finding out the effect of Case Based Learning (CBL) model toward student science generic skill on Crude Oil lesson at the eleventh grade.  This research was conducted on Crude Oil lesson in the Academic Year of 2023/2024 at State Senior High School 3 Tapung. Quasi-experiment method was used in this research. The subjects of this research were 2 classes experiment and control groups, selected by using purposive sampling technique. Based on the research findings, posttest showed that the significance score (2-tailed) 0.038 was lower than 0.05, so it showed that there was a significant difference between experiment and control groups. Besides, N-gain mean of experiment group science generic skill was 0.52, and the control group was 0.41. Therefore, it could be concluded that CBL model affected student science generic skill on Crude Oil lesson at the eleventh grade. The research findings were expected to help teachers in increasing student science generic skill by using CBL model in the learning process.Keywords : Case Based Learning, Science Generic Skill, Crude Oil